Gerakan Ekonomi Islam Pada Era Pra Kemerdekaan - Riswan Rambe (Universitas Islam Negeri Sumatera Utara, 2018)
This research is aimed to know the background of economic movement conducted by SDI, Muhammadiyah and NU and analyzing the obstacles faced by SDI, Muhammadiyah and NU in Islamic economic movement. The research method used in this research uses library study method with qualitative approach. The result of this conclusion can be concluded that the patterns of SDI movement, Muhammadiyah, and NU have a contemporary, traditional-conservative economic ideology. The existence of a positive influence on the movement of SDI to the Muslim community, among others, the lifting of indigenous traders became strong, and eliminating discriminatory treatment to indigenous traders. A good influence on the Muhammadiyah movement to the people, both their growing economy and their human resources, is better, one example of the pre-economy by establishing the BMT of the Ummah and the Muhammadiyah Bank. And also the economy of the people due to the influence of Nahdlatut Tujjar and establish the Shirkah Muawwanah cooperative in pesantren-pesantren. The movements provided by SDI, Muhammadiyah, and NU to the community have had a positive impact on the social, economic, social, and social issues.